Website Quality, Brand Image, And Brand Trust On Repurchase Intention Through Customer Satisfaction As Intervening Variables - Ida Bagus Nyoman Udayana; Lusia Tria Hatmanti Hutami; Yuli Endar Yani (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine the effect of website quality, brand image, brand trust on repuschase intention through customer satisfaction as an intervening variable (study on consumers at Mutiara Cosmetics Yogyakarta stores). This research was conducted in the city of Yogyakarta by distributing questionnaires to a research sample of 100 respondents through probability sampling technique. The data were analyzed using SPSS 25. The results of this study indicate that the website quality variable has a significant effect on customer satisfaction, obtaining a significant value of 0.000. The variable brand image has an effect on customer satisfaction, obtaining a significant value of 0.050. The variable brand trust has an effect on customer satisfaction, obtaining a significant value of 0.031. The customer satisfaction variable has no effect on repurchase intention to obtain a significant value of 0.254. The variable wesite quality has an effect on repurchase intention has a significant value of 0.002. The variable brand image has an effect on repurchase intention to obtain a significant value of 0.000. The variable brand trust has an effect on repurchase intention to obtain a significant value of 0.045.